2020
DOI: 10.3389/fphys.2020.00284
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Arterial Elastance as a Ventriculo-Arterial Coupling Index: An Experimental Animal Study

Abstract: Dynamic arterial elastance (Ea dyn), the ratio between arterial pulse pressure and stroke volume changes during respiration, has been postulated as an index of the coupling between the left ventricle (LV) and the arterial system. We aimed to confirm this hypothesis using the gold-standard for defining LV contractility, afterload, and evaluating ventricular-arterial (VA) coupling and LV efficiency during different loading and contractile experimental conditions. Twelve Yorkshire healthy female pigs submitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 58 publications
3
36
1
Order By: Relevance
“…These findings corroborate previous results about the compound nature of Ea dyn and the impact of both cardiac and arterial factors ( Monge Garcia et al, 2020 ). While net changes in Ea, a net measure of LV afterload, were negatively associated with Ea dyn , variations in heart rate did so positively ( Monge Garcia et al, 2017 ; de Courson et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings corroborate previous results about the compound nature of Ea dyn and the impact of both cardiac and arterial factors ( Monge Garcia et al, 2020 ). While net changes in Ea, a net measure of LV afterload, were negatively associated with Ea dyn , variations in heart rate did so positively ( Monge Garcia et al, 2017 ; de Courson et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Septic animals also showed a significant decrease in arterial tone, as reflected by an increase in net arterial compliance ( Cherpanath et al, 2014 ). This study, together with our previous observations about the impact of changes in arterial load ( Monge Garcia et al, 2017 ), support the notion that Ea dyn does not represent a real measure of central arterial tone nor an index of the arterial stiffness, and that the concept of Ea dyn as a variable describing LV afterload should be avoided ( Monge Garcia et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The dynamic arterial elastance can be easely measured with invasive and non-invasive hemodynamic devices [ 29 31 ]. Dynamic arterial elastance is a real time indicator of the interaction between the heart and the vascular system that has been challenged as an indicator of V-A coupling [ 32 , 33 ]. Several clinical studies have demonstrated that dynamic arterial elastance is able to predict SV and blood pressure response to FC or norepinephrine, and it can be used to optimize treatment [ 17 , 29 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%